Molecular insights on xenoestrogenic potential of zearalenone-14-glucoside through a mixed in vitro/in silico approach. (October 2017) - Dellafiora, Luca; Ruotolo, Roberta; Perotti, Alessio; Cirlini, Martina; Galaverna, Gianni; Cozzini, Pietro; Buschini, Annamaria; Dall'Asta, Chiara
Abstract: The mycotoxin zearalenone may contaminate food and feed worldwide upon infections by Fusarium spp. of plants and raw materials intended for human and animal consumption. Currently, contamination by zearalenone and congeners pose concern for health due to xenoestrogenic effects. However, while zearalenone and the main reduced metabolites are well-known xenoestrogens, some plant metabolites that may enter the food chain have been observed aside. Among them, zearalenone-14-glucoside may be abundant in the edible parts of infected plants, thereby entering significantly the human diet and animal feeding. On the basis of previous works, the lack of xenoestrogenicity for this compound per se was taken for granted, while neglecting the direct proof of estrogenic activity and considering the hydrolysis as a possible source of estrogenically active metabolites. The present work investigated the xenoestrogenicity of zearalenone-14-glucoside, in comparison to zearalenone, deepening the underlying molecular mechanisms through an integrated in vitro/in silico approach. On the basis of our results, zearalenone-14-glucoside effectively stimulated a xenoestrogenic response in cells, but such stimulus can be entirely attributable to the hydrolysis phenomenon, as the glycosylated form turned out to be unable to effectively bind and activate the estrogens receptors. Graphical abstract: